As mudanças metodológicas do orçamento participativo de João Pessoa, suas causas e efeitos (2013-2020) - Macêdo, Jackson Azevedo de (2022)
This research seeks to analyze the possible influences and their consequences in the metamorphoses of the methodological application of the Participatory Budget, more specifically those carried out in the city of João Pessoa - PB, between the years 2013 to 2020. To this end, we analyze two possible aspects for these influences: the changes in the political conjuncture resulting from the various party affiliations of the city manager in the period, because during the time frame, the then Mayor Luciano Cartaxo was affiliated to three different parties (PT, PSD and PV), or if such methodological changes are just adjustments structures in order to increase the efficiency of the participatory instrument for the execution of public works and policies in the municipality. The work is supported by concepts of political project, the understanding of the governing coalition and the understanding of methodologies and methodological aspects of the various metamorphoses of the OP execution models. Still, the relationships formed from the Institutional Design that we call here "rainbow of relationships". To analyze these influences and their consequences, we analyzed aspects of social participation and the execution of demands in the period. The research is based on an exploratory case study (empirical and documentary), using a qualitative approach as a way to seek as many instruments and elements as possible for the development of the project. Still, it was conceived from the perspective of a militant researcher who empirically experienced the PB in the city of João Pessoa, since, during the 2014 and 2015 cycles, I was the municipal secretary of the instrument in the city. Thus, it was found that the stability of public policy programs such as the PB is directly linked to the good execution and efficiency of these instruments. In the case of João Pessoa, political conjunctures were incapable of producing substantial changes in PB methodologies and practices in the city. The main result found is that such methodological changes are structural adjustments in order to increase the efficiency of the participatory instrument for the execution of public works and policies in the specific case of the experience in the capital of Paraíba.